Oil sludge for improving surface quality of aluminum alloy round ingot and improvement method

By using multiple sets of zinc powder and conductive fibers of different particle sizes in the oil sludge, a dense conductive grid structure is formed, which solves the problem of uneven distribution of the oil sludge, and significantly improves the corrosion resistance and hardness performance of the aluminum alloy round ingot.

CN119775897APending Publication Date: 2025-04-08GUANGXI TIANCHENG ALUMINUM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510050131.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, oil sludge is unevenly distributed on the surface of aluminum alloy round ingots, which affects the effect of improving surface quality.

Method used

Multiple groups of zinc powder with different particle sizes and carbon fibers and copper fibers with conductive properties are used to form a dense conductive grid structure through mixing and ultrasonic treatment, which improves the distribution uniformity and conductive properties of zinc powder.

Benefits of technology

The surface quality of aluminum alloy round ingots has been significantly improved, corrosion resistance and hardness performance have been enhanced, a uniform protective barrier has been formed, and the use effect of sludge has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239729700000111
    Figure BDA0005239729700000111
Patent Text Reader

Abstract

The present invention relates to the technical field of oil sludge, specifically to an oil sludge and an improvement method for improving the surface quality of aluminum alloy round ingots: comprising the following raw materials in weight percentage: 30-40% zinc powder, 8-10% resin, 4-6% mica powder, 2-4% fumed silica, 2-4% fiber material, 1-3% benzotriazole, 1-3% antioxidant, 1-3% thickener, 1-3% leveling agent, 0.08-0.12% lanthanum, 0.08-0.12% cerium, and the balance is grease. In the present invention, zinc powders of different particle sizes improve the corrosion resistance of aluminum alloys. By adding carbon fibers and copper fibers with conductive properties, the conductive fiber material can establish a conductive grid structure between zinc powders, promote rapid electron transmission, and enable the cathode protection current to be evenly and quickly distributed to the surface of the aluminum alloy, thereby improving the surface quality of the aluminum alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil sludge, in particular to oil sludge used for improving the surface quality of aluminum alloy round ingots and an improvement method. Background Art

[0002] The sludge used to improve the surface quality of aluminum alloy round ingots is a multi-component functional material that can adhere to the surface of the aluminum alloy to form a protective layer, which can effectively improve the surface quality of the aluminum alloy round ingots.

[0003] In the prior art, when using oil sludge to improve the surface quality of aluminum alloy round ingots, after the oil sludge is coated on the surface of the aluminum alloy, the material that plays a protective role in the oil sludge is prone to uneven distribution, which affects the effect of the oil sludge on improving the surface quality of the aluminum alloy. Based on this, the present invention provides an oil sludge for improving the surface quality of aluminum alloy round ingots and an improvement method. Summary of the invention

[0004] The purpose of the present invention is to provide an oil sludge and an improvement method for improving the surface quality of aluminum alloy round ingots. The aluminum alloy round ingots obtained by the improved treatment of the present invention not only have good corrosion resistance, but also have excellent hardness performance, which effectively improves the use effect of the oil sludge.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides an oil sludge for improving the surface quality of aluminum alloy round ingots, comprising the following raw materials in weight percentage: 30-40% zinc powder, 8-10% resin, 4-6% mica powder, 2-4% fumed silica, 2-4% fiber material, 1-3% benzotriazole, 1-3% antioxidant, 1-3% thickener, 1-3% leveling agent, 0.08-0.12% lanthanum, 0.08-0.12% cerium, and the balance is grease;

[0007] The zinc powder is divided into component A, component B and component C, the mass ratio of component A, component B and component C is 1:1.5:2, the particle size of the zinc powder of component A is 10-20 μm, the particle size of the zinc powder of component B is 30-40 μm, and the particle size of the zinc powder of component C is 40-50 μm.

[0008] Furthermore, the fiber material consists of carbon fibers and copper fibers, and the mass ratio of the carbon fibers to the copper fibers is 6:4.

[0009] Furthermore, the carbon fiber has a diameter of 6 to 10 μm, the copper fiber has a diameter of 8 to 12 μm, and the lengths of the carbon fiber and the copper fiber are both 0.2 to 0.4 mm.

[0010] Furthermore, the fiber material is prepared by the following method: carbon fiber and copper fiber are immersed in an immersion liquid for 20 to 30 minutes, and the carbon fiber and copper fiber are rinsed with deionized water after immersion, and then placed in an oven after rinsing, and the oven is set at 70 to 80° C. for drying for 40 to 50 minutes to obtain the fiber material.

[0011] Furthermore, the soaking liquid is prepared by mixing aminopropyltriethoxysilane, water and ethanol, and the mass ratio of aminopropyltriethoxysilane, water and ethanol is 1:5:7.

[0012] Furthermore, the grease is prepared by mixing mineral oil and polyol ester, the mass ratio of the mineral oil and the polyol ester is 8:2, the antioxidant is dilauryl thiodipropionate, and the resin is epoxy resin.

[0013] Furthermore, the thickener is selected from at least one of bentonite and polytetrafluoroethylene powder, and the leveling agent is selected from at least one of polydimethylsiloxane, perfluoroalkylethyl acrylate, and methyl silicone oil.

[0014] Furthermore, the zinc powder, fiber material, mica powder, lanthanum and cerium are mixed to obtain an additive. The preparation method of the additive is as follows: add C component zinc powder into a mixer, add B component zinc powder and fiber material into the mixer, set the mixer to 180-220r / min for mixing for 16-20min, then add A component zinc powder, mica powder, lanthanum and cerium, set the mixer to 420-460r / min for mixing for 26-30min, add clean water at a uniform speed during the second mixing process, send it into an oven after mixing is completed, set the oven to 70-80°C for drying for 40-50min, then send it into an ultrasonic generator, set the ultrasonic generator to a frequency of 60-70kHz, and the processing time is 8-12min to obtain the additive.

[0015] Furthermore, the mass of the clean water is 16-20% of the mass of the zinc powder.

[0016] In a second aspect, the present invention further provides a method for improving the surface quality of an aluminum alloy round ingot by removing oil sludge, comprising the following steps:

[0017] S1: Preparation of oil sludge: weigh additives, resin, fumed silica, benzotriazole, antioxidant, thickener, leveling agent and grease as needed and add them into a mixer. Set the mixer to 80-120r / min and mix for 16-20min to obtain oil sludge;

[0018] S2: Workpiece processing: The surface of the aluminum alloy round ingot is cleaned, degreased and dried;

[0019] S3: Surface treatment, immersing the aluminum alloy round ingot that has been cleaned, degreased and dried in oil sludge for 10 to 12 minutes. The oil sludge is continuously stirred during the immersion process. After the immersion is completed, the aluminum alloy round ingot is taken out of the oil sludge, and allowed to stand for 10 to 20 minutes at room temperature. It is then placed in a high-temperature vacuum oven and treated at 500 to 600°C for 8 to 12 minutes. The oven is kept warm for 20 minutes to form a coating on the surface of the aluminum alloy round ingot. After cooling to room temperature, the surface coating of the aluminum alloy round ingot is finely polished, that is, the surface quality of the aluminum alloy round ingot is improved by using oil sludge.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. In the present invention, by selecting a plurality of groups of zinc powders with different particle sizes, zinc powders with different particle sizes can be filled in the oil mud, and small-particle zinc powder can be filled in the gaps between large-particle zinc powders to form a dense structure, which not only improves the strength but also forms a denser barrier, thereby improving the corrosion resistance of aluminum alloys. By adding carbon fiber and copper fiber with conductive properties, the conductive fiber material can establish a conductive grid structure between the zinc powders, promote rapid electron transmission, and enable the cathodic protection current to be evenly and quickly distributed to the surface of the aluminum alloy, thereby improving the surface quality of the aluminum alloy.

[0022] 2. In the present invention, by adding lanthanum and cerium in the preparation of additives, rare earth elements can improve the electrode potential of zinc powder. By pre-preparing the additives, the uniformity of zinc powder distribution can be improved, and a more uniform protective barrier can be formed for the surface of the aluminum alloy, further improving the surface quality of the aluminum alloy. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0024] The present embodiment provides an oil sludge for improving the surface quality of aluminum alloy round ingots, comprising the following raw materials in weight percentage: 30-40% zinc powder, 8-10% resin, 4-6% mica powder, 2-4% fumed silica, 2-4% fiber material, 1-3% benzotriazole, 1-3% antioxidant, 1-3% thickener, 1-3% leveling agent, 0.08-0.12% lanthanum, 0.08-0.12% cerium, and the balance is grease;

[0025] The zinc powder is divided into component A, component B and component C. The mass ratio of component A, component B and component C is 1:1.5:2. The particle size of the zinc powder of component A is 10-20 μm, the particle size of the zinc powder of component B is 30-40 μm, and the particle size of the zinc powder of component C is 40-50 μm.

[0026] In some embodiments, the fiber material consists of carbon fiber and copper fiber, and the mass ratio of the carbon fiber to the copper fiber is 6:4.

[0027] In some embodiments, the carbon fiber has a diameter of 6 to 10 μm, the copper fiber has a diameter of 8 to 12 μm, and the lengths of the carbon fiber and the copper fiber are both 0.2 to 0.4 mm.

[0028] In some embodiments, the fiber material is prepared by the following method: carbon fiber and copper fiber are immersed in an immersion liquid for 20 to 30 minutes, and the carbon fiber and copper fiber are rinsed with deionized water after immersion. After rinsing, they are placed in an oven and dried at 70 to 80°C for 40 to 50 minutes to obtain the fiber material.

[0029] In some embodiments, the soaking liquid is prepared by mixing aminopropyltriethoxysilane, water and ethanol, and the mass ratio of aminopropyltriethoxysilane, water and ethanol is 1:5:7.

[0030] In some embodiments, the grease is prepared by mixing mineral oil and polyol ester, the mass ratio of mineral oil to polyol ester is 8:2, the antioxidant is dilauryl thiodipropionate, and the resin is epoxy resin.

[0031] In some embodiments, the thickener is selected from at least one of bentonite and polytetrafluoroethylene powder, and the leveling agent is selected from at least one of polydimethylsiloxane, perfluoroalkylethyl acrylate, and methyl silicone oil.

[0032] In some embodiments, zinc powder, fiber material, mica powder, lanthanum and cerium are mixed to obtain an additive, and the preparation method of the additive is as follows: add component C zinc powder into a mixer, add component B zinc powder and fiber material into the mixer, set the mixer to 180-220r / min for mixing for 16-20min, then add component A zinc powder, mica powder, lanthanum and cerium, set the mixer to 420-460r / min for mixing for 26-30min, add clean water at a uniform speed during the second mixing process, send it into an oven after mixing is completed, set the oven to 70-80℃ for drying for 40-50min, then send it into an ultrasonic generator, set the ultrasonic generator to a frequency of 60-70kHz, and the processing time is 8-12min to obtain the additive.

[0033] In some embodiments, the mass of the clean water is 16-20% of the mass of the zinc powder.

[0034] In some embodiments, a method for improving the surface quality of an aluminum alloy round ingot by using oil sludge includes the following steps:

[0035] S1: Preparation of oil sludge: weigh additives, resin, fumed silica, benzotriazole, antioxidant, thickener, leveling agent and grease as needed and add them into a mixer. Set the mixer to 80-120r / min and mix for 16-20min to obtain oil sludge;

[0036] S2: Workpiece processing: The surface of the aluminum alloy round ingot is cleaned, degreased and dried;

[0037] S3: Surface treatment, immersing the aluminum alloy round ingot that has been cleaned, degreased and dried in oil sludge for 10 to 12 minutes. The oil sludge is continuously stirred during the immersion process. After the immersion is completed, the aluminum alloy round ingot is taken out of the oil sludge, and allowed to stand for 10 to 20 minutes at room temperature. It is then placed in a high-temperature vacuum oven and treated at 500 to 600°C for 8 to 12 minutes. The oven is kept warm for 20 minutes to form a coating on the surface of the aluminum alloy round ingot. After cooling to room temperature, the surface coating of the aluminum alloy round ingot is finely polished, that is, the surface quality of the aluminum alloy round ingot is improved by using oil sludge.

[0038] In the present embodiment, by selecting a plurality of groups of zinc powders with different particle sizes, zinc powders with different particle sizes can be filled with each other in the oil mud, and small-size zinc powder can be filled in the gaps between large-size zinc powders to form a dense structure, which not only improves the strength but also forms a denser barrier, thereby improving the corrosion resistance of aluminum alloys. By adding carbon fiber and copper fiber with conductive properties, the conductive fiber material can establish a conductive grid structure between zinc powders, promote rapid electron transmission, and enable the cathodic protection current to be evenly and quickly distributed to the surface of the aluminum alloy, thereby improving the surface quality of the aluminum alloy. By adding lanthanum and cerium in the preparation of additives, rare earth elements can improve the electrode potential of zinc powder. By pre-preparing the additives, the uniformity of zinc powder distribution can be improved, and a more uniform protective barrier can be formed for the surface of the aluminum alloy, thereby further improving the surface quality of the aluminum alloy.

[0039] Based on the above embodiments, the following experiments were performed:

[0040] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.

[0041] Experiment 1:

[0042] The invention comprises the following raw materials in weight percentage: 30% zinc powder, 8% resin, 4% mica powder, 2% fumed silica, 2% fiber material, 1% benzotriazole, 1% antioxidant, 1% thickener, 1% leveling agent, 0.08% lanthanum, 0.08% cerium, and the balance is oil;

[0043] The zinc powder is divided into component A, component B and component C, the mass ratio of component A, component B and component C is 1:1.5:2, the particle size of the zinc powder of component A is 10 μm, the particle size of the zinc powder of component B is 30 μm, and the particle size of the zinc powder of component C is 40 μm. The fiber material is composed of carbon fiber and copper fiber, the mass ratio of carbon fiber to copper fiber is 6:4, the diameter of carbon fiber is 6 μm, the diameter of copper fiber is 8 μm, and the length of carbon fiber and copper fiber is 0.2 mm.

[0044] The fiber material is prepared by the following method: carbon fiber and copper fiber are immersed in an immersion liquid for 20 minutes, and the carbon fiber and copper fiber are rinsed with deionized water after immersion. After rinsing, they are placed in an oven and dried at 70°C for 40 minutes to obtain the fiber material. The immersion liquid is prepared by mixing aminopropyl triethoxysilane, water and ethanol, and the mass ratio of aminopropyl triethoxysilane, water and ethanol is 1:5:7.

[0045] The grease is prepared by mixing mineral oil and polyol ester, the mass ratio of mineral oil to polyol ester is 8:2, dilauryl thiodipropionate is selected as the antioxidant, and epoxy resin is selected as the resin.

[0046] Bentonite is used as thickener and polydimethylsiloxane is used as leveling agent.

[0047] Zinc powder, fiber material, mica powder, lanthanum and cerium are mixed to obtain an additive. The preparation method of the additive is as follows: C component zinc powder is added into a mixer, B component zinc powder and fiber material are added into the mixer, the mixer is set at 180r / min for mixing for 16min, then A component zinc powder, mica powder, lanthanum and cerium are added, the mixer is set at 420r / min for mixing for 26min, clean water is added at a uniform speed during the second mixing process, and after mixing, the additive is sent into an oven, the oven is set at 70°C for drying for 40min, and then the additive is sent into an ultrasonic generator, the ultrasonic generator is set at a frequency of 60kHz, the processing time is 8min, and the additive is obtained. The mass of clean water is 16% of the mass of zinc powder.

[0048] S1: Preparation of oil sludge: Additives, resin, fumed silica, benzotriazole, antioxidant, thickener, leveling agent and grease are weighed as needed and added into a mixer. The mixer is set at 80r / min for 16 minutes to obtain oil sludge;

[0049] S2: Workpiece processing: The surface of the aluminum alloy round ingot is cleaned, degreased and dried;

[0050] S3: Surface treatment: immerse the aluminum alloy round ingot after cleaning, degreasing and drying in oil sludge for 10 minutes. The oil sludge is kept in a stirring state during the immersion process. After the immersion is completed, the aluminum alloy round ingot is taken out of the oil sludge, and allowed to stand for 10 minutes at room temperature. Then, it is sent to a high-temperature vacuum oven and set at 500℃ for 8 minutes. The oven is kept warm for 20 minutes to form a coating on the surface of the aluminum alloy round ingot. After cooling to room temperature, the surface coating of the aluminum alloy round ingot is finely polished, that is, the surface quality of the aluminum alloy round ingot is improved by using oil sludge.

[0051] Experiment 2:

[0052] The invention comprises the following raw materials in weight percentage: 35% zinc powder, 9% resin, 5% mica powder, 3% fumed silica, 3% fiber material, 2% benzotriazole, 2% antioxidant, 2% thickener, 2% leveling agent, 0.1% lanthanum, 0.1% cerium, and the balance is oil;

[0053] The zinc powder is divided into component A, component B and component C, the mass ratio of component A, component B and component C is 1:1.5:2, the particle size of the zinc powder of component A is 15 μm, the particle size of the zinc powder of component B is 35 μm, and the particle size of the zinc powder of component C is 45 μm. The fiber material is composed of carbon fiber and copper fiber, the mass ratio of carbon fiber to copper fiber is 6:4, the diameter of carbon fiber is 8 μm, the diameter of copper fiber is 10 μm, and the length of carbon fiber and copper fiber is 0.3 mm.

[0054] The fiber material is prepared by the following method: carbon fiber and copper fiber are immersed in an immersion liquid for 25 minutes, and the carbon fiber and copper fiber are rinsed with deionized water after immersion. After rinsing, they are placed in an oven and dried at 75°C for 45 minutes to obtain the fiber material. The immersion liquid is prepared by mixing aminopropyl triethoxysilane, water and ethanol, and the mass ratio of aminopropyl triethoxysilane, water and ethanol is 1:5:7.

[0055] The grease is prepared by mixing mineral oil and polyol ester, the mass ratio of mineral oil to polyol ester is 8:2, dilauryl thiodipropionate is selected as the antioxidant, and epoxy resin is selected as the resin.

[0056] The thickener is polytetrafluoroethylene powder and the leveling agent is perfluoroalkyl ethyl acrylate.

[0057] Zinc powder, fiber material, mica powder, lanthanum and cerium are mixed to obtain an additive. The preparation method of the additive is as follows: C component zinc powder is added into a mixer, B component zinc powder and fiber material are added into the mixer, the mixer is set to 200r / min for mixing for 18min, then A component zinc powder, mica powder, lanthanum and cerium are added, the mixer is set to 440r / min for mixing for 28min, clean water is added at a uniform speed during the second mixing process, and after mixing, the mixture is sent into an oven, the oven is set to 75°C for drying for 45min, and then the mixture is sent into an ultrasonic generator, the ultrasonic generator is set to a frequency of 65kHz, the processing time is 10min, and the additive is obtained, and the mass of the clean water is 18% of the mass of the zinc powder.

[0058] S1: Preparation of oil sludge: weigh additives, resin, fumed silica, benzotriazole, antioxidant, thickener, leveling agent and grease as needed and add them into a mixer. Set the mixer to 100 r / min and mix for 18 minutes to obtain oil sludge;

[0059] S2: Workpiece processing: The surface of the aluminum alloy round ingot is cleaned, degreased and dried;

[0060] S3: Surface treatment: The aluminum alloy round ingot that has been cleaned, degreased and dried is immersed in the oil sludge for 11 minutes. The oil sludge is continuously stirred during the immersion process. After the immersion is completed, the aluminum alloy round ingot is taken out of the oil sludge, and allowed to stand for 15 minutes at room temperature. It is then sent to a high-temperature vacuum oven and set at 550°C for 10 minutes. The oven is kept warm for 20 minutes to form a coating on the surface of the aluminum alloy round ingot. After cooling to room temperature, the surface coating of the aluminum alloy round ingot is finely polished, that is, the surface quality of the aluminum alloy round ingot is improved by using the oil sludge.

[0061] Experiment 3:

[0062] The invention comprises the following raw materials in weight percentage: 40% zinc powder, 10% resin, 6% mica powder, 4% fumed silica, 4% fiber material, 3% benzotriazole, 3% antioxidant, 3% thickener, 3% leveling agent, 0.12% lanthanum, 0.12% cerium, and the balance is oil;

[0063] The zinc powder is divided into component A, component B and component C, the mass ratio of component A, component B and component C is 1:1.5:2, the particle size of the zinc powder of component A is 20 μm, the particle size of the zinc powder of component B is 40 μm, and the particle size of the zinc powder of component C is 50 μm. The fiber material is composed of carbon fiber and copper fiber, the mass ratio of carbon fiber to copper fiber is 6:4, the diameter of carbon fiber is 10 μm, the diameter of copper fiber is 12 μm, and the length of carbon fiber and copper fiber is 0.4 mm.

[0064] The fiber material is prepared by the following method: carbon fiber and copper fiber are immersed in an immersion liquid for 30 minutes, and the carbon fiber and copper fiber are rinsed with deionized water after immersion. After rinsing, they are placed in an oven and dried at 80°C for 50 minutes to obtain the fiber material. The immersion liquid is prepared by mixing aminopropyl triethoxysilane, water and ethanol, and the mass ratio of aminopropyl triethoxysilane, water and ethanol is 1:5:7.

[0065] The grease is prepared by mixing mineral oil and polyol ester, the mass ratio of mineral oil to polyol ester is 8:2, dilauryl thiodipropionate is selected as the antioxidant, and epoxy resin is selected as the resin.

[0066] Bentonite is used as thickener and methyl silicone oil is used as leveling agent.

[0067] Zinc powder, fiber material, mica powder, lanthanum and cerium are mixed to obtain an additive. The preparation method of the additive is as follows: C component zinc powder is added into a mixer, B component zinc powder and fiber material are added into the mixer, the mixer is set at 220r / min for mixing for 20min, then A component zinc powder, mica powder, lanthanum and cerium are added, the mixer is set at 460r / min for mixing for 30min, clean water is added at a uniform speed during the second mixing process, and after mixing, the mixture is sent into an oven, the oven is set at 80°C for drying for 50min, and then the mixture is sent into an ultrasonic generator, the ultrasonic generator is set at a frequency of 70kHz, the processing time is 12min, and the additive is obtained. The mass of the clean water is 20% of the mass of the zinc powder.

[0068] S1: Preparation of oil sludge: weigh additives, resin, fumed silica, benzotriazole, antioxidant, thickener, leveling agent and grease as needed and add them into a mixer. Set the mixer to 120r / min and mix for 20min to obtain oil sludge;

[0069] S2: Workpiece processing: The surface of the aluminum alloy round ingot is cleaned, degreased and dried;

[0070] S3: Surface treatment: immerse the aluminum alloy round ingot after cleaning, degreasing and drying in oil sludge for 12 minutes. The oil sludge is kept in a stirring state during the immersion process. After the immersion is completed, the aluminum alloy round ingot is taken out of the oil sludge, and allowed to stand for 20 minutes at room temperature. Then, it is sent to a high-temperature vacuum oven and set at 600℃ for 12 minutes. The oven is kept warm for 20 minutes to form a coating on the surface of the aluminum alloy round ingot. After cooling to room temperature, the surface coating of the aluminum alloy round ingot is finely polished, that is, the surface quality of the aluminum alloy round ingot is improved by using oil sludge.

[0071] Comparative Example 1: The difference between this comparative example and Experiment 1 is that this comparative example does not contain lanthanum and cerium.

[0072] Comparative Example 2: The difference between this comparative example and Experiment 1 is that this comparative example does not contain mica powder.

[0073] Comparative Example 3: The difference between this comparative example and Experiment 1 is that this comparative example does not contain fiber material.

[0074] Comparative Example 4: The difference between this comparative example and Experiment 1 is that in this comparative example, an equal amount of zinc powder is used to replace the additive.

[0075] Performance test: Performance test was performed on the aluminum alloy round ingots obtained by the improved treatment of Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4.

[0076] In the performance test, the corrosion depth and corrosion mass loss of the aluminum alloy round ingots obtained by the improved treatment of Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were tested in accordance with the standard GB / T 7998-2023 "Evaluation Method for Intergranular Corrosion Sensitivity of Aluminum Alloys", and the obtained test data are recorded in the following table:

[0077]

[0078] It can be seen that the corrosion resistance and hardness performance of the aluminum alloy round ingots obtained by the improved treatment of Comparative Examples 1, 2, 3, and 4 are lower than those of Experiments 1, 2, and 3; this shows that: by selecting a plurality of groups of zinc powders with different particle sizes, zinc powders of different particle sizes can be filled with each other in the oil mud, and small-particle zinc powder can be filled in the gaps between large-particle zinc powders to form a dense structure, which not only improves the strength but also forms a relatively dense barrier, thereby improving the corrosion resistance of the aluminum alloy. By adding carbon fiber and copper fiber with conductive properties, the conductive fiber material can establish a conductive grid structure between the zinc powders, promote rapid electron transmission, and enable the cathodic protection current to be evenly and quickly distributed to the surface of the aluminum alloy, thereby improving the surface quality of the aluminum alloy.

[0079] By comparing and analyzing the relevant data in the table, it can be seen that the aluminum alloy round ingot obtained by the improvement treatment of the present invention not only has good corrosion resistance, but also has excellent hardness performance. This shows that the sludge and improvement method for improving the surface quality of aluminum alloy round ingots provided by the present invention have a broader market prospect and are more suitable for promotion.

[0080] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0081] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An oil sludge for improving the surface quality of aluminum alloy round ingots, characterized by: The invention comprises the following raw materials in weight percentage: 30-40% zinc powder, 8-10% resin, 4-6% mica powder, 2-4% fumed silica, 2-4% fiber material, 1-3% benzotriazole, 1-3% antioxidant, 1-3% thickener, 1-3% leveling agent, 0.08-0.12% lanthanum, 0.08-0.12% cerium, and the balance is oil; The zinc powder is divided into component A, component B and component C, the mass ratio of component A, component B and component C is 1:1.5:2, the particle size of the zinc powder of component A is 10-20 μm, the particle size of the zinc powder of component B is 30-40 μm, and the particle size of the zinc powder of component C is 40-50 μm.

2. The oil sludge for improving the surface quality of aluminum alloy round ingot according to claim 1, characterized in that: The fiber material consists of carbon fiber and copper fiber, and the mass ratio of the carbon fiber to the copper fiber is 6:

4.

3. The oil sludge for improving the surface quality of aluminum alloy round ingot according to claim 2, characterized in that: The carbon fiber has a diameter of 6 to 10 μm, the copper fiber has a diameter of 8 to 12 μm, and the lengths of the carbon fiber and the copper fiber are both 0.2 to 0.4 mm.

4. The oil sludge for improving the surface quality of aluminum alloy round ingot according to claim 2, characterized in that: The fiber material is prepared by the following method: the carbon fiber and the copper fiber are immersed in an immersion liquid for 20 to 30 minutes, the carbon fiber and the copper fiber are rinsed with deionized water after immersion, and the rinsed carbon fiber and the copper fiber are placed in an oven at 70 to 80° C. for drying for 40 to 50 minutes to prepare the fiber material.

5. The oil sludge for improving the surface quality of aluminum alloy round ingot according to claim 4, characterized in that: The soaking liquid is prepared by mixing aminopropyl triethoxysilane, water and ethanol, and the mass ratio of the aminopropyl triethoxysilane, water and ethanol is 1:5:

7.

6. The oil sludge for improving the surface quality of aluminum alloy round ingot according to claim 1, characterized in that: The grease is prepared by mixing mineral oil and polyol ester, the mass ratio of the mineral oil to the polyol ester is 8:2, the antioxidant is dilauryl thiodipropionate, and the resin is epoxy resin.

7. The oil sludge for improving the surface quality of aluminum alloy round ingot according to claim 1, characterized in that: The thickener is selected from at least one of bentonite and polytetrafluoroethylene powder, and the leveling agent is selected from at least one of polydimethylsiloxane, perfluoroalkylethyl acrylate, and methyl silicone oil.

8. The oil sludge for improving the surface quality of aluminum alloy round ingot according to claim 1, characterized in that: The zinc powder, fiber material, mica powder, lanthanum and cerium are mixed to obtain an additive. The preparation method of the additive is as follows: C component zinc powder is added to a mixer, B component zinc powder and fiber material are added to the mixer, the mixer is set to 180-220r / min for mixing for 16-20min, then A component zinc powder, mica powder, lanthanum and cerium are added, the mixer is set to 420-460r / min for mixing for 26-30min, clean water is added at a uniform speed during the second mixing process, and after mixing, the additive is sent to an oven, the oven is set to 70-80°C for drying for 40-50min, and then the additive is sent to an ultrasonic generator, the ultrasonic generator is set to a frequency of 60-70kHz, and the processing time is 8-12min to obtain the additive.

9. The oil sludge for improving the surface quality of aluminum alloy round ingot according to claim 8, characterized in that: The mass of the clean water is 16-20% of the mass of the zinc powder.

10. A method for improving the surface quality of an aluminum alloy round ingot by using oil sludge according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Preparation of oil sludge: weigh additives, resin, fumed silica, benzotriazole, antioxidant, thickener, leveling agent and grease as needed and add them into a mixer. Set the mixer to 80-120r / min and mix for 16-20min to obtain oil sludge; S2: Workpiece processing: The surface of the aluminum alloy round ingot is cleaned, degreased and dried; S3: Surface treatment, immersing the aluminum alloy round ingot that has been cleaned, degreased and dried in oil sludge for 10 to 12 minutes. The oil sludge is continuously stirred during the immersion process. After the immersion is completed, the aluminum alloy round ingot is taken out of the oil sludge, and allowed to stand for 10 to 20 minutes at room temperature. It is then placed in a high-temperature vacuum oven and treated at 500 to 600°C for 8 to 12 minutes. The oven is kept warm for 20 minutes to form a coating on the surface of the aluminum alloy round ingot. After cooling to room temperature, the surface coating of the aluminum alloy round ingot is finely polished, that is, the surface quality of the aluminum alloy round ingot is improved by using oil sludge.